Agriculture Supply Chain Optimization in East Java - Ferry Prasetyia; Farah Wulandari Pangestuty; Andhika Paratama Herlambang (Journal of International Conference Proceedings, 2022)
The goal of this study is to look at the value chain for strategic agricultural commodities in East Java and optimize the supply chain. Input-output analysis, supply chain descriptive analysis, institutional pattern analysis, trading margin analysis, value chain analysis, root cause analysis, and the Analytical Hierarchy Process are among the analytical methods used. According to the findings of this study, sugar cane, cayenne pepper, and corn are three strategic agricultural commodities in East Java with a relatively long supply chain. However, the study discovered that among other supply chain actors, farmers and breeders have the lowest price margins, while collectors and wholesalers have the highest. This implies that there may be opportunities to improve the supply chain for these commodities by addressing the problems that farmers and breeders face.